2011
DOI: 10.1002/jor.21494
|View full text |Cite
|
Sign up to set email alerts
|

The (−1486T/C) promoter polymorphism of the TLR‐9 gene is associated with end‐stage knee osteoarthritis in a Chinese population

Abstract: Based on the recent observation that Toll-like receptors (TLRs) may be involved in the pathogenesis of osteoarthritis (OA) we explored the possibility that human TLR gene polymorphisms are associated with OA. Two separate populations were studied in a two-stage case-control study with a total of 503 OA patients and 428 healthy controls. The TLR-2, TLR-4, and TLR-9 genotypes were assessed by real-time polymerase chain reaction. Our data demonstrated a lack of association among TLR-2, TLR-4, and TLR-9 (T-1237C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
(23 reference statements)
2
23
3
Order By: Relevance
“…Accumulating studies reported that TLR-mediated responses were key inducers of pro-inflammatory cytokines, which directly or indirectly resulted in development of lymphatic pathology [5659]. Studies reported that ligands for TLRs (including TLR-2, 3, 4, 9) induced or exacerbated arthritis in experimental models[52, 60]. NF-κB has been reported to regulate expressions of genes involved in OA [61].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies reported that TLR-mediated responses were key inducers of pro-inflammatory cytokines, which directly or indirectly resulted in development of lymphatic pathology [5659]. Studies reported that ligands for TLRs (including TLR-2, 3, 4, 9) induced or exacerbated arthritis in experimental models[52, 60]. NF-κB has been reported to regulate expressions of genes involved in OA [61].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study demonstrated that TLR2 and TLR4 signals are important in mediating catabolic responses and in increasing MMP-3 and MMP-13 production in murine cartilage explants (63). A recent genetic study in a Chinese population identified a TLR-9 polymorphism that is associated with the presence of radiographic knee OA (102). This report did not reveal an association with common TLR-2 or -4 polymorphisms, and how TLR-9 is linked to increased risk of OA is not yet clear.…”
Section: Pathways That May Promote Synovitis In Oamentioning
confidence: 99%
“…Also, it seems that the TLR‐2 induced expression of collagenase contributes to the catabolism of cartilage affected by OA, suggesting that modulation of TLR expression or activation in chondrocytes can be a path that might block cartilage degradation . Results of recent studies show that some TLR polymorphisms are associated with predisposition to primary knee OA (KOA) in the Chinese population …”
mentioning
confidence: 99%